The language of symbols in prehistoric Anatolia - Yakar, Jak (Documenta Praehistorica, 2005)
The conceptual and ritual background of symbolism in the prehistoric art of Anatolia should be investigated within the socio-economic background of the pertinent Neolithic and Chalcolithic societies. Since the adoption of farming did not totally replace the more traditional modes of subsistence, it is doubtful that the supernatural world-order envisaged by earlier hunter-gatherers would have been entirely altered by new spiritual concepts.
Keywords: Anatolija; arheološke najdbe; neolitik; simboli; symbol; simbolizem; šamanizem